2005
DOI: 10.1523/jneurosci.1976-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Versican in the Developing Brain: Lamina-Specific Expression in Interneuronal Subsets and Role in Presynaptic Maturation

Abstract: Chondroitin sulfate proteoglycans (CSPGs) of the extracellular matrix help stabilize synaptic connections in the postnatal brain and impede regeneration after injury. Here, we show that a CSPG of the lectican family, versican, also promotes presynaptic maturation in the developing brain. In the embryonic chick optic tectum, versican is expressed selectively by subsets of interneurons confined to the retinorecipient laminae, in which retinal axons arborize and form synapses. It is a major receptor for the Vicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 81 publications
0
40
0
1
Order By: Relevance
“…Although the majority of previous findings show that versican is made by glia, double-label in situ hybridization showed that, in the embryonic chick tectum, versican is expressed by local interneurons that also express reelin, substance-P receptor, or neuropilin-1 but not by cells expressing the glial marker glutamine synthetase. These experiments also revealed that versican expression is graded across the depth of the tectal layers [Yamagata and Sanes, (2005) (Fig. 1), which could have implications for layer-specific axon guidance.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Although the majority of previous findings show that versican is made by glia, double-label in situ hybridization showed that, in the embryonic chick tectum, versican is expressed by local interneurons that also express reelin, substance-P receptor, or neuropilin-1 but not by cells expressing the glial marker glutamine synthetase. These experiments also revealed that versican expression is graded across the depth of the tectal layers [Yamagata and Sanes, (2005) (Fig. 1), which could have implications for layer-specific axon guidance.…”
Section: Introductionmentioning
confidence: 77%
“…A recent article by Yamagata and Sanes in The Journal of Neuroscience [Yamagata and Sanes, (2005) (http://www/jneurosci. org/cgi/content/full/25/37/8457)] provides new insights into these questions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations